2005
DOI: 10.1002/jctb.1384
|View full text |Cite
|
Sign up to set email alerts
|

Decolourisation of dyes and dyehouse effluent in a bubble‐column reactor by heterogeneous catalytic ozonation

Abstract: The decolourisation of aqueous solutions of dyes by ozonation with various heterogeneous catalysts using a bubble-column reactor was investigated. The catalysts studied were hydrated alumina, activated carbon and ferric oxide supported on silica. The optimum catalyst concentration and pH for decolourisation were determined in each case. Hydrated alumina and silica-supported ferric oxide showed excellent catalytic activity under acidic conditions, whereas activated carbon was found to be effective under both ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…(10)-(15)) [15,18,26,39] and O 3 /MnO 2 systems (Eqs. (16)- (20)) [15][16][17]40]. Dye + OH • → products Mn(II) can react with O 3 to produce hydrous manganese oxide (Mn(OH 2 )) in situ, which subsequently attacks the pollutant molecules and accelerates degradation [11].…”
Section: O 3 Uv/tio 2 and Uv/tio 2 /O 3 Systemsmentioning
confidence: 99%
“…(10)-(15)) [15,18,26,39] and O 3 /MnO 2 systems (Eqs. (16)- (20)) [15][16][17]40]. Dye + OH • → products Mn(II) can react with O 3 to produce hydrous manganese oxide (Mn(OH 2 )) in situ, which subsequently attacks the pollutant molecules and accelerates degradation [11].…”
Section: O 3 Uv/tio 2 and Uv/tio 2 /O 3 Systemsmentioning
confidence: 99%
“…These groups could either be formed on the HA molecules or be acidic compounds that split from HA molecules as a result of the oxidation. Synchronously, pH is usually considered as an important parameter of the ozonation kinetics of organic substances, 21,22 hence HA ozonation in phosphate buffer (pH 7) was further investigated. Results showed that the HA ozonation in buffer solution agreed with the pseudo-first-order equation, as can be seen in Fig.…”
Section: Kinetics Of Ha Ozonationmentioning
confidence: 99%
“…The RB5 solution was scanned by a spectrophotometer (Metertech, SP-830, Taiwan) from 320 nm to 900 nm, and the optical absorption curve plotted. Decolourization of RB5 was determined using the characteristic peak absorbance (598 nm), a similar method was reported for detecting the dyes 7 and RB5 mineralization was determined by results of a TOC analyzer (Tekmar, Dohrmann Phoenix 8000, USA). The Zeta potential of the magnetic catalyst (SiO 2 /Fe 3 O 4 ) in the aqueous phase was measured using a Zetasizer Nano Instrument (Nano ZS, Red badge ZEN 3600, UK) with the solution pH adjusted between 2 and 7.5 by adding NaOH and HCl.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…1 -3 These studies show that industrialscale AOPs for water and waste-water treatment have been developed for the oxidation of various refractory and hazardous organics in the presence of oxidants such as UV/H 2 7 allow faster removal of organic pollutants because such catalysts improve the oxidizing power of O 3 and thus significantly reduce the cost of the ozonation process. The use of ozone coupled with effective, inexpensive, and non-toxic mobilized/immobilized heterogeneous catalysts for the treatment of waste-water has been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation